Anti-Drugs Youth Cadre Training: An Effort to Strengthen the Perception and Knowledge of Madrasah Aliyah Students in South Jakarta - Fransiskus Samuel Renaldi; Khrisna Pangeran (Universitas Malahayati Lampung, 2026)
ABSTRACT Adolescent drug abuse is a public health concern influenced by access to substances, peer pressure, and exposure to digital information. This activity aimed to describe Madrasah Aliyah Mannaratul Islam students’ perceptions and knowledge of drug-abuse risks and to assess immediate knowledge change following anti-drug youth cadre training. This community-service evaluation used a qualitative descriptive design with content analysis of verbatim interview responses from 70 students in grades 10–12, supported by univariate analysis of respondent characteristics and pretest–posttest knowledge scores. Most students perceived drugs as deadly and addictive (80%); 93% lived in a complete family structure, and 26% had received counseling during the previous six months. Knowledge scores increased from 87.5% to 96.0% after the educational session. The findings indicate that knowledge improvement should be reinforced through interactive education, digital literacy, stronger family communication, and peer-led intervention grounded in madrasa values. Keywords: Drug Perception, Adolescent Knowledge, Madrasa Prevention, Drug Education.